Indiscriminate Use of Antibiotics for COVID-19 Treatment in South Asian Countries is a Threat for Future Pandemics Due to Antibiotic Resistance - Sohel Daria; Md. Rabiul Islam (SAGE Publishing, 2022)
The COVID-19 pandemic has put enormous strain on the global public health and healthcare systems. Here we aimed to assess the prevalence and impact of indiscriminate use of antibiotics for COVID-19 treatment in south Asian countries. We observed the indiscriminate use of antibiotics in south Asian countries and other similar parts of the world. Along with vaccines, people in poor and developing countries have been taking antibiotics and some other medications without proper jurisdiction during the waves of the COVID-19 pandemic. We all know that COVID-19 is a viral disease, and only a few patients might have bacterial co-infections. Therefore, the role of antibiotics is ambiguous in most COVID-19 cases. Consequently, the overuse of antibiotics would cause antimicrobial resistance that has the potential to become a 2-edged sword after the COVID-19 pandemic era. Our findings emphasize the judicious use of antibiotics in COVID-19 therapy, especially in poor and developing countries across the globe.